A Large Gastric Duplication (Choristoma) in an Adult Mimicking a Mucinous Cystic Tumor of the Pancreas - Cienfuegos, Javier A; Hernández-Lizoáin, José Luis; Idoate, Carlos Pastor; Zozaya, Gabriel; Bueno, Álvaro; Sola, Jesús Javier (JOP. Journal of the Pancreas, 2010)
Gastric duplication represents a very rare entity in the adult population. Most of the symptoms are due to the presence of ectopic gastric mucosa (30-35% of cases), gastrointestinal bleeding or perforation or neoplasm formation. We report a case of gastric duplication in an adult mimicking a mucinous cystic neoplasm of the pancreas. Image: Gross appearance of the cystic tumor in the pancreas tail.